Effectiveness of national board certified teachers in terms of classroom environment, attitudes and achievement among secondary science students - Helding, Karen A. (Curtin University, 2006)
A United States organization, called the National Board of Professional Teaching Standards (NBPTS), was initiated to strengthen the pedagogy of teaching and, subsequently, improve student achievement. The purpose of this study was to investigate the effectiveness of the NBPTS in terms of whether National Board Certified (NBC) teachers are effective in promoting positive classroom environments and student attitudes and in enhancing student achievement. The sample consisted of 927 Grade 8 and 10 science students from 12 secondary schools. Altogether, 443 students in 21 classes comprised the NBC teacher group and 484 students in 17 classes comprised the non-NBC teacher group. Students completed a learning environment questionnaire, the What Is Happening In this Class? (WIHIC), and an attitude scale based on the Test Of Science-Related Attitude (TOSRA). Scores from the science portion of the Florida Comprehensive Assessment Test FCAT, a state-mandated examination, were collected to measure achievement. This research is unique in that it is the first time that a learning environments study has included a sample of National Board Certified (NBC) and non-NBC teachers in order to compare their effectiveness in terms of secondary students' perceptions of their science learning environment, attitudes toward science, and science achievement. The study revealed that the revised version of the WIHIC and the modified attitude scale are valid and reliable instruments for assessing perceptions of the classroom environment and attitudes toward science among secondary science students in Miami-Dade County, Florida.In addition, a much stronger association with learning environment was found for students' attitude than for students' achievement. The contributions and significance of this study are not only that it adds to the area of research that pertains to the efficacy of NBC teachers, but it also adds to the field of learning environments research. This study is useful because it could be replicated to provide additional empirical evidence about the effect National Board teachers have on students in the classroom and add to the growth of educational data on the impact of National Teacher Certification and classroom learning environments research.